Spiro Metric and Some Sellctive Immunological Changes Among 49 Cases of Different Respiratory Diseases - Mahmud, Sayeed; Alamgir, ANM; Hoque, Md Gofranul; Husain, Md Anwar; Nahar, Nazmun (Journal of Chittagong Medical College Teachers' Association, 2012)
Total 49 patients having different types of respiratory diseases were selected to evaluate their Spiro metric and IgG, IGE related blood changes. Out of these 49 respondents, 27 were females and 22 were males. 9 patients were more than 60+ years of age. Among the sufferers, 10 had bronchial asthma, 22 patients had bronchitis. Illness duration varied from <1 month ot >30 years; 14 male respondents had smoking habit. 50% of the respondents had hereditary trend of present respiratory disease, 5 cases had drug addiction. Chest X-ray was performed for 48 cases, abnormality revealed in 13 cases. Out of40 routing examination of blood, 13 had eosonophilia and raised ESR values. 15 respondents had eosonophil count 10-15%, 4 had >20%. Spirometry performed on 28 respondents. 07(25%) of the cases revealed abnormal feature-out of these, 02(29%) were obstructive and 5(71%) were restrictive1. Mean FVC and FEV1 of the restrictive cases were 59.42% and 52.68% respectively. Both are <80% of the predicted normal value, FEV1/FVC was 0.88 (<90% of predicted normal). In case of 02 obstructive types, FEV1 /FVC was 0.86 (<90% of predicted normal). Immunological changes of blood were observed through serum IgG and serum IgE level estimations. Mean serum IgG level of 49 respondents was 16.27 g/L, SD ± 4.33, t=7.73 at P48<0.001, showing notable variation with the reference value for serum IgG. Mean serum IgE level was 1051.72 iu/ml, SD ± 915.87 iu/ml, t=7.37 which significantly differ from normal reference serum level of IgE at P48<0.001 irrespective of age of the respondents. Mean FVC, FEV1 were highest in obstructive cases-156.4%, 135.9% and lowest in restrictive cases-59.42%, 61.9% respectively. The ratio of FEV1 and FVC was observed in normal cases as 90.87%, Predicted FVC among smokers was 105.70% and in non-smokers, it was 117.19%. Significand differences of mean FVC was observed between smokers (3.77 ± 1.26) and non-smokers (3.94 ±2.19); F=3.02, P.05. Gender discrimination of lung functions was significantly different in case of FVC, in males it was 4.25 ±2.08 and in females, it was 3.18 ±1.16;F=3.22, P>.10. Among the 49 individuals serum IgGT and serum IgE values spread scattered, regression line passed through the intercept value 11.69 on Y-axis. JCMCTA 2011; 22(2): 37-43